2019
DOI: 10.3390/s19214729
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Classification of Running Fatigue Using Change-Point Segmentation

Abstract: Blood lactate accumulation is a crucial fatigue indicator during sports training. Previous studies have predicted cycling fatigue using surface-electromyography (sEMG) to non-invasively estimate lactate concentration in blood. This study used sEMG to predict muscle fatigue while running and proposes a novel method for the automatic classification of running fatigue based on sEMG. Data were acquired from 12 runners during an incremental treadmill running-test using sEMG sensors placed on the vastus-lateralis, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…A machine learning approach to estimate the level of fatigue during running has been demonstrated previously by Khan et al using sEMG and blood lactate analysis [ 50 ]. However, this study only segmented fatigue into three classes (aerobic, anaerobic, and recovery phases based on blood lactate levels) whereas we were able to estimate fatigue accurately over a range of RPE from 13 to 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A machine learning approach to estimate the level of fatigue during running has been demonstrated previously by Khan et al using sEMG and blood lactate analysis [ 50 ]. However, this study only segmented fatigue into three classes (aerobic, anaerobic, and recovery phases based on blood lactate levels) whereas we were able to estimate fatigue accurately over a range of RPE from 13 to 20.…”
Section: Resultsmentioning
confidence: 99%
“…One major limitation of estimating fatigue level is the variability of kinematic changes between individuals [ 17 , 26 ]. For this reason, most of the previous studies have proposed intra-participant models [ 37 , 50 , 52 ]. However, using a motor learning approach may overcome this limitation and we aim to investigate this in future studies with larger and more diverse samples.…”
Section: Resultsmentioning
confidence: 99%
“…A reason to neglect the time course of the axial peak tibial acceleration may be that relevant changes in such a signal are usually not easily discernible by sight. The technique of change-point analysis may be of use to detect event(s) at which the underlying dynamics of a signal changes over time [17][18][19][20][21][22][23]. Several types of control statistics have been used for change-point discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical step of human motion classification is the selection of classification technology. Based on the above feature extraction methods, researchers mainly used support a vector machine (SVM), decision tree (DT), random forest (RF), nearest neighbor (KNN), and naive Bayes (NB) to classify human motion [ 27 , 28 , 29 , 30 , 31 , 32 ]. Rohit Gupta et al used a time-domain analysis method to classify the movement of the lower limbs, and concluded that the linear discriminant analysis (LDA) classifier had the highest accuracy, and for different feature subsets, the classification accuracy was between 89% and 99% [ 33 ].…”
Section: Introductionmentioning
confidence: 99%